AN ANALYSIS OF TRANSPOSITION PROCEDURE OFPASSIVE VOICE IN THE NOVEL "IRRESISTIBLE FORCES"BY DANIELLE STEEL TRANSLATED BY GITA K - Disy Hermaretha, - (2009)
This paper is entitled An Analysis of Transposition Procedure of Passive Voice in the Novel "Irresistible Forces" by Danielle Steel Translated by Gita K. It is aimed at analyzing the transposition process of voice elements (actor, action, and receiver). It describes the kinds of transposition, the translation methods, and the background of the occurrence in translating passive voice. The theory used to categorize the transposition occurrence is Newmark's theory which formulates four categories (type I, II, III and IV). The sample is a number of transposed passive voices taken from the novel Irresistible Forces and its translation version Kekuatan Mahadasyat.